A physics-informed and data-enhanced tensile stress-strain model for UHPFRC. (15th June 2023) - Liu, Wei-He; Zhang, Lu-Wen; Dai, Jian-Guo
Highlights: A one-dimensional multiphase model predicted well tensile behaviors of UHPFRC with various matrix strengths, fiber contents and geometries. Physical-consistent strength and ultimate strain models of UHPFRC were proposed, trained by model-generated data and enhanced by experimental data. The proposed strength and ultimate strain models predicted experimental data satisfactorily with mean absolute percentage errors (MAPE) of 12% and 25.3%, respectively. Higher matrix strengths lead to higher tensile strength, less cracks with larger crack widths, and lower ductility of UHPFRC, due to snubbing effects and multi-crack interactions. Abstract: Despite the rapid developments in fundamental investigations and engineering applications of ultra-high-performance fiber reinforced concrete (UHPFRC), there is still lacking of a reliable tensile stress-strain model for UHPFRC in design guidelines. A generalized tensile stress-strain model for UHPFRC was developed for the first time. Through properly identifying unified model parameters, widely acknowledged experimental results were successfully reproduced by using a one-dimensional finite element model (FEM). A rich database was generated and granted with physics by the FEM model. Physical-consistent strength, ultimate strain and stress-strain models of UHPFRC were proposed, trained by model-generated data, and enhanced by experimental data. The proposed strength model and ultimate strain model predicted extensive experimental results with reasonable accuracy, giving mean absolute percentage errors (MAPE) of 12% and 25.3%, respectively. The established stress-strain model also predicted satisfactorily the full-range stress-strain curves tested by different research groups. It was evidenced that higher mean matrix cracking strength leads to higher ultimate strengths, less cracks, higher crack widths of UHPFRC at the ultimate state. This was elaborated for the first time, as caused by the dual action of snubbing effects and multi-crack interactions.